Central serous chorioretinopathy imaging biomarkers. Issue 4 (7th December 2020) - Singh, Sumit Randhir; Iovino, Claudio; Zur, Dinah; Masarwa, Dua; Iglicki, Matias; Gujar, Ramkailash; Lupidi, Marco; Maltsev, Dmitrii S; Bousquet, Elodie; Bencheqroun, Mehdi; Amoroso, Francesca; Lima, Luiz H; et al.
Abstract : Purpose: To identify the factors predicting the visual and anatomical outcomes in eyes with central serous chorioretinopathy (CSCR) through 12 months. Methods: Patients with diagnosis of CSCR, either acute or chronic, were included in this multicentric, retrospective study. Demographic factors; systemic risk factors; central macular thickness (CMT), subfoveal choroidal thickness (SFCT), linear extent of ellipsoid zone (EZ) and interdigitation zone damage on optical coherence tomography; details of leak on fluorescein angiography and indocyanine green angiography were included as predictors of anatomical and visual outcomes. Regression analysis was performed to correlate the changes in best corrected visual acuity (BCVA) and resolution of disease activity. Results: A total of 231 eyes of 201 patients with a mean age (49.7±11.8 years) were analysed. A total of 97 and 134 eyes were classified as acute and chronic CSCR. BCVA (0.35±0.31 to 0.24±0.34; p<0.001), baseline optical coherence tomography (OCT) parameters including CMT (p<0.001), subretinal fluid (SRF) height (p<0.001) and SFCT (p=0.05) showed a significant change through 12 months. Multivariate regression analysis showed change in CMT (p≤0.01) and SRF height at baseline (p=0.05) as factors predictive of good visual outcome. Logistic regression analysis revealed changes in both CMT (p=0.009) and SFCT (p=0.01) through 12 months to correlate with the resolution of disease. Conclusion: OCT parameters such as changes in both CMT and SFCT along with subfoveal EZ damage can be predictive of disease resolution whereas changes in CMT and baseline SRF height correlate well with changes in BCVA through 12 months.